Latent Profile of Academic Resilience and Friendship Satisfaction in Relation to Achievement Emotions among School-Aged Adolescents - Apriliana, I Putu Agus (The Indonesian Institute of Science and Technology Research, 2026)
Adolescence represents a critical developmental phase characterized by escalating academic demands and increasingly salient peer relationships, both of which play a central role in shaping students’ achievement-related emotional experiences. Although academic resilience and friendship satisfaction are well-established protective resources, prior research has predominantly examined these constructs in isolation, leaving their joint configurations and emotional consequences underexplored, particularly within resource-constrained and culturally contextualized educational settings. Adopting a person-centered approach, this study identified latent profiles of school-aged adolescents based on combined patterns of academic resilience and friendship satisfaction and examined profile differences in positive and negative achievement emotions. Data were collected from 582 randomly selected adolescents in Kupang City, Indonesia, using validated measures of academic resilience, friendship satisfaction, and achievement emotions. Latent profile analysis followed by multivariate analysis of variance revealed four distinct profiles with meaningful emotional differentiation. Adolescents in the buffered resilience profile exhibited the most adaptive emotional patterns, characterized by high positive emotions (enjoyment, hope & pride) and low negative emotions (anger, anxiety, shame, hopeless & boredom) in learning and classroom contexts. In contrast, adolescents in the relationally constrained profile reported low positive emotions alongside elevated negative emotions in both contexts. Notably, high friendship satisfaction alone, as observed in the relationally compensated profile, was insufficient to offset low academic resilience. These findings extend the Theoretical Resilience and Relational Load Linkage framework by highlighting the synergistic role of individual adaptive capacities and relational resources in shaping adolescents’ achievement emotions, offering actionable implications for school-based interventions and educational policy.